Perancangan Video Animasi 3d Iklan Layanan Masyarakat Sebagai Pengenalan Pemilahan Sampah Kepada Masyarakat Kota Mojokerto - Maulana Arsaq, Ahmad; Samodra, Joko; Wardani, Nuril Kusuma (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2024)
The increasing population growth every year results in a number of social problems, one of which is waste management. If permitted, this issue can lead to various problems related to aesthetics, sanitation, health, and the environment. Mojokerto City is one of the cities experiencing an annual increase in waste volume, indicating that the community in Mojokerto has limited knowledge about waste sorting. Therefore, the aim of this research is to design a 3D animated Public Service Advertisement for community service that introduces waste sorting to the people of Mojokerto City, and then to test the results of the design. The Public Service Advertisement is created using 3D animation with the Multimedia Development Life Cycle (MDLC) method, which includes several stages: concept, design, material collecting, assembly, testing, and distribution. This 3D animated Public Service Advertisement has a duration of 2 minutes and 40 seconds, in mp4 format, with a resolution of 1280x720. It is distributed through social media platforms, specifically YouTube. The Public Service Advertisement. has been tested with media experts resulting in 79.44%, Then, it was tested with content experts resulting in 85.67%, and finally, media testing was conducted with the audience, yielding a result of 84.55%. So that this 3D animated Public Service Advertisement can be utilized as an introduction to waste management for the people of Mojokerto City. It is hoped that the presence of this 3D animated community service advertisement will be beneficial to the entire community of Mojokerto City and help reduce improper waste disposal.